ANALISIS EMISI CO2 DI KAMPUS UIN SYARIF HIDAYATULLAH JAKARTA - A Silvan Erusani; Nurmaya Arofah (Program Pascasarjana Universitas Riau, 2022)
The purpose of this study was to determine carbon dioxide (CO2) emissions generated by the population of the academic community (lecturers, employees and students) and motor vehicle transportation in the campus of UIN Syarif Hidayatullah Jakarta, which is located on Jalan Juanda as the study location because it is the center of the campus. The method used in this research is survey and calculation. The calculation results show that CO2 emissions produced by humans from all residents on campus 1 UIN Syarif Hidayatullah Jakarta, totaling 24,126 people, produce CO2 emissions of 3,136 kg/hour or equivalent to 25,091 kg/day or equivalent to 6,021,849 kg/year. Meanwhile, the amount of CO2 emissions from motor vehicles (cars and motorcycles) is 4299,121 kg/hour or the equivalent of 8,254.3 tons/year.